The zero heat flux method and sweat loss modeling in sports: attempts of next generation sports information systems - Janta, M.; Höschele, N.; Senner, V. (Procedia Engineering, 2016)
Today professional and amateur endurance athletes commonly use biofeedback systems to monitor their training and competition pace. Body core temperature and sweat loss are crucial factors influencing physical capabilities. Unfortunately, current gold standards are invasive and therefore impractical in active situations. Several non-intrusive technologies or models have been proposed, but partially are still unsuitable for active applications, not user friendly or lack knowledge on physiological relations. This paper is a first attempt for new information systems in sports and primarily assesses the Zero Heat Flux Method (ZHF) compared to aural temperatures during activity in two environments and four body sites. Furthermore, sweat loss has been analysed in various controlled experiments presented as simple modelling approach. Results showed that during activity in this set up, optimally 66% of differences in the zero heat flux method were within common core temperature deviations of ±0.5 °C. Deviations varied highly across sites, the two conditions and individuals. The same is reflected from relations between body core temperature and sweat loss, since correlation coefficients increase with a more detailed subgrouping. In conclusion, it seems that slight modifications on the sensor assembly e.g. on insulation and size could partially solve remaining deviations. On contrast it's likely that skin wetness remains a problem. Due to manifold individual and environmental influences on sweat rate, insufficient technologies and impracticable models, it remains unclear how sweat loss could be reliably measured or predicted. From today's knowledge a further attempt could be using local sweat composition as predictor of blood sodium levels that potentially could describe hypo- and even hyper-hydration.